Tracheostomy in childhood: review of the literature on complications and mortality over the last three decades - Dal’Astra,Ana Paula Ligoski (2017)
Abstract Introduction: Tracheostomy is a procedure with unique characteristics when used on pediatric patients due to the greater technical difficulty and higher morbidity and mortality rates relative to the procedure in adults. In recent decades, there have been significant changes in the medical care available to children, particularly for those who need intensive care. Surgical conditions have also improved, and there has been an advent of new equipment and medications. These advances have brought changes to both tracheostomy indications and tracheostomy complications. Objective: To perform a review of the articles published over the last three decades on the complications and mortality associated with tracheostomies in children. Methods: Articles were selected from the Cochrane, Latin American and Caribbean Health Sciences Literature, SciELO, National Library of Medicine (Medline Plus), and PubMed online databases. The articles selected had been published between January 1985 and December 2014, and the data was compared using the Chi-square test. Results: A total of 3797 articles were chosen, 47 of which were used as the basis for this review. When the three decades were evaluated as a whole, an increase in tracheostomies in male children under one year of age was found. The most common complications during the period analyzed in descending order of frequency were granuloma, infection, and obstruction of the cannula, accidental decannulation, and post-decannulation tracheocutaneous fistula. In the second and third decades of the review, granulomas represented the most common complication; in the first decade of the review, pneumothoraces were the most common. Mortality associated with tracheostomy ranged from 0% to 5.9%, while overall mortality ranged from 2.2% to 59%. In addition, the review included four studies on premature and/or very underweight infants who had undergone tracheostomies; the studies reported evidence of higher mortality in this age group to be largely associated with underlying diseases. Conclusion: Improved surgical techniques and intensive care, the creation of new medications, and vaccines have all redefined the main complications and the mortality rates of tracheostomy in children. It is a safe procedure that increases chances of survival in those who require the prolonged use of mechanical ventilation.